HEC-HMS based rainfall-runoff model for Punpun river basin. Issue 5 (8th April 2022) - Ranjan, Shashi; Singh, Vivekanand
Abstract: Various hydrological models were used in different river basins to simulate the runoff on available rainfall, land use and soil property data. The HEC-HMS model is used by several researchers to estimate the water potential of the basin through rainfall-runoff modeling. In this study, a rainfall-runoff model for the Punpun river basin has been developed using HEC-HMS. Daily rainfall and runoff data from the years 2005 to 2017 were used for the development of model. ArcGIS has been used to analyze the hydrological parameters, preparation of LULC, soil and slope maps for the computation of curve number as input into the HEC-HMS model. Daily, monthly and monsoonal rainfall-runoff models have been developed. The performance of all the models has been evaluated using statistical indices–coefficient of determination (R 2 ), Nash-Sutcliffe efficiency (NSE), percent bias (PBIAS) and RMSE-observations standard deviation ratio (RSR). R 2 and NSE values for all the models are greater than 0.75 and PBIAS is less than 10, which shows very good results from all the models except the daily model, in which NSE values are less than 0.75. Based on statistical indices, the monthly model performs better than the daily and monsoonal models. HIGHLIGHTS: A rainfall-runoff model for the Punpun river basin has been developed. Various statistical indices have been computed to check the performance of the model. Comparison of daily, monthly and monsoonal models have been made. Graphical Abstract